102k views
2 votes
. Is (4,-3) a solution to the following system of equations?

X - y = 4
2x + y = 5
(Use elimination method)

User Bansi
by
4.7k points

1 Answer

4 votes

Answer:

No. The correct solution is (3,-1)

Explanation:

Since we are using elimination method, we can go ahead and see that we can cancel "-y" from the first equation and "+y" from the second equation.

Once we do that, we go ahead add the like terms and get 3x = 9

Then, we divide by 3 on each side and get x = 3

Now, we can take that value of x and plugin to any of the original 2 equations we started with.

Say we plugin x = 3 into the second equation.. it will turn to, 2(3) + y = 5

Then we solve for y.

2(3) + y = 5

6 + y = 5

6 - 1 = 5

y = -1

There, we found our x value and our y value, (3,-1) :)

User Nhuluseda
by
4.2k points